Normativas internas adoptadas por el estado peruano sobre el derecho de acceso a internet y su adecuación a estándares internacionales - Hemeryth Montoya, Michelle Alexandra (2024)
The objective of this work was to analyze to what extent the internal regulations regulated by the Peruvian State conform to the international standards established with respect to guaranteeing the right of access to the Internet. Taking into account the growing relevance of the Internet in contemporary society, where information and knowledge are interconnected, it is recognized internationally as a human right by organizations such as the Inter-American Human Rights System (SIDH). Consequently, Peru, in order to be part of it, must harmonize its internal regulatory framework to ensure respect for this right. To carry out this work, exhaustive documentary research was carried out that involved the location, recovery, evaluation and analysis of documentary sources, as well as the thorough review of internal normative and legislative documents related to the subject addressed. Finally, the study has shown that, although there are regulatory advances and initiatives in our current legal framework, regarding the regulations that regulate access to the Internet, it was possible to identify a couple of international standards established on the subject that have not yet been adopted by our national regulations. This highlights the importance of strengthening our national regulations to guarantee quality and equal access to the Internet for all Peruvians.